Antioxidant properties and bioactivity of three marine microalgae on human cancer cell lines - Helen Herbert; Rachel Parkes; Maria Elena Barone; Adam McDonnell; Sabrina Picciotto; Giorgia Adamo; Angela Paterna; Mauro Manno; Antonella Bongiovanni; Nicolas Touzet; Eva Campion (Applied Phycology)
Marine microalgae offer significant potential as sustainably cultivable microorganisms for the biorefining of a diverse array of functional metabolites. In this study, three species of marine microalgae, Tetraselmis chuii Butcher CCAP 66/21B (Chlorophyte), Phaeodactylum tricornutum Bohlin CCAP 1052/1 (Diatom) and Amphidinium carterae Hulburt CCAP 1102/8 (Dinoflagellate), were batch cultivated and their biomass retrieved for analysis in terms of pigment and fatty acid composition as well as bioactivity potential. Sequential solvent maceration of the biomass returned extracts was used to determine antioxidant capacity and assess their growth inhibition potential against A549 (a human lung carcinoma) and MCF-7 (a breast carcinoma) cell lines. The extracts of A. carterae showed higher antioxidant capacity (≤ 33.5 μmol Trolox Equivalent mg Recovered Dried Material‒1) compared to the other extracts. No major cytotoxic activity nor production of reactive oxygen species was observed using the extracts of T. chuii and P. tricornutum. However, the methanolic extraction of A. carterae inhibited the growth of both A549 and MCF-7 cells (< 4%) at 25, 50 and 100 µg ml−1 concentrations, as determined using the MTS assay and AO/PI cell staining. Microalgal metabolites have the potential for practical applications in a variety of industrial sectors. The absence of toxicity and substantial antioxidant potential of extracts of T. chuii and P. tricornutum confirm their suitability for incorporation into animal feeds or human nutrition supplements. A. carterae also appears to be a promising source of bioactives that can be further valorized via multi-compound biorefinery pipelines.